Occhiolism and Coded Bodies: Current Social Challenges. - Sălcudean, Ileana Nicoleta; Scînteianu, Maria; Zhu, Anna Decheng (Caietele Echinox, 2026)
The debate between "performed" and "digital" or "embodied" and "disembodied" (Anne Harris) brings forth new challenges and discussions. We detect a new type of interaction as an aggregated repository of the absent/ present body, a mêlée identity (Jean-Luc Nancy) subsequently charting aspects of the aesthetic and the social sphere. Yet, the awareness of "occhiolism", characteristics of both the artist and the spectator, sheds a new light on the technological advancements and the new ways of actualization of performances (art-spectator) interactivity in and beyond exhibitions. The paper has as a case study a digital interactive art exhibition: Occhio, which was the result of the cultural-artistic grants received from the University of Babeș-Bolyai (Cluj-Napoca, March 2021).